Planning for Pedestrians with a participatory multicriteria approach (2020)
The design of accessible walking routes needs to take into account the different stakeholders’ preferences and factors affecting walking. It is a complex issue which policy-makers should deal with to foster sustainable mobility. A participatory multicriteria decision analysis approach is presented to help the planning and designing of pedestrian routes, based on a sound analysis of factors affecting walking behavior and the attributes of the roads, and a stakeholder-driven evaluation of the same. A group of different stakeholders has been involved to select the criteria for designing pedestrian routes in the city center of Cartagena (Colombia). Some of them have been selected based on the results of a social network analysis (SNA) to be involved as key stakeholders for the evaluation of the selected criteria through an analytic network process (ANP). An index to measure the importance of each criterion in designing pedestrian routes has been obtained. Results provide valuable inputs to understand how to redesign and reconfigure streets for pedestrians in a city so as to improve walkability and foster a shift toward active and sustainable transport modes.